2000
DOI: 10.1177/073724770002500205
|View full text |Cite
|
Sign up to set email alerts
|

Parent, Teacher, and Self-Report of Problem and Adaptive Behaviors in Children and Adolescents with Asperger Syndrome

Abstract: The present study examined perceptions of the social problems and adaptive behaviors of children and youth with Asperger Syndrome. Parents and teachers used the Behavior Assessment System for Children (BASC) (Reynolds & Kamphaus, 1992) to evaluate 20 children and youth with Asperger Syndrome. In addition, the 20 students using the BASC self-report instrument evaluated their social problems and adaptive behavior. Findings are discussed relative to better understanding and planning for the needs of children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
66
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 48 publications
(95 reference statements)
6
66
1
Order By: Relevance
“…Poor ER has been implicated in a range of emotional problems in children with ASD, such as anxiety [Gadow, Devincent, Pomeroy, & Azizian, 2005;Green, Gilchrist, Burton, & Cox, 2000;Simonoff et al, 2008;Wood & Gadow, 2010], depressive symptoms [Barnhill et al, 2000;Pouw, Rieffe, Stockmann, & Gadow, 2013;Zablotsky, Bradshaw, Anderson, & Law, 2013], and anger [Rieffe, Camodeca, Pouw, Lange, & Stockmann, 2012;Scarpa & Reyes, 2011]. A review of the literature reveals a relative lack of studies of ER in adults with ASD.…”
mentioning
confidence: 99%
“…Poor ER has been implicated in a range of emotional problems in children with ASD, such as anxiety [Gadow, Devincent, Pomeroy, & Azizian, 2005;Green, Gilchrist, Burton, & Cox, 2000;Simonoff et al, 2008;Wood & Gadow, 2010], depressive symptoms [Barnhill et al, 2000;Pouw, Rieffe, Stockmann, & Gadow, 2013;Zablotsky, Bradshaw, Anderson, & Law, 2013], and anger [Rieffe, Camodeca, Pouw, Lange, & Stockmann, 2012;Scarpa & Reyes, 2011]. A review of the literature reveals a relative lack of studies of ER in adults with ASD.…”
mentioning
confidence: 99%
“…As noted earlier, and reflected in the literature (Barnhill et al, 2000b;Frith, 1991), even though frequently motivated to be near to and to socially interact with peers and adults, students with AS are deficient in age-appropriate, reciprocal social interaction skills such as those required to participate in cooperative play and related activities.…”
Section: Behavioral Interventions and Supports For Students With Aspementioning
confidence: 81%
“…In one of the few studies that attempted to identify the nature of behavior problems and adaptive behavior in students with AS, Barnhill et al (2000b) compared behavior rating scale inventories completed by parents, teachers, and students. The results revealed that parents had significantly greater concern about the behavior and social skills of their .…”
Section: Behavioral and Emotional Characteristics Of Students With Asmentioning
confidence: 99%
“…They will make repeated inappropriate efforts to interact with a peer and continue to repeat the unsuccessful overture becoming increasing frustrated and ultimately acting out. (Attwood, 2007;Barnhill, Hagiwara, Myles, Simpson, Brick, & Griswold, 2000;Dewey, 1999;Dissanayake, 2004;Harris, 1994;Harris & Powers, 1984;Myles & Adreon, 2001;Myles & Simpson, 1998;Tantum, 2000).…”
mentioning
confidence: 99%
“…Yet, references are repeatedly made within these studies to the important role parents play in the child's life and the crucial need to include them in the planning, behavior management, and skill development. (Attwood, 2007(Attwood, , 1998Barnhill et al, 2000;Klin, Volkmar, & Sparrow, 2000;Myles & Adreon, 2001;Ozonoff, Dawson, & MacPartland, 2002;Schuntermann, 2002;Tantum, 2000).…”
mentioning
confidence: 99%